Democracy : Development and Improvement - The Role of Participation and Deliberation - Becak, Rubens (2016)
Despite being a relatively recent phenomenon, democracy seems to have been raised to the level of a ubiquitous system so its existence and enshrinement are truly understood as a postulate. In this sense it’s very important to understand it’s evolution from the advent of the Modernity specially to understand how the model evolved adopting the representation by the political parties. Despite its qualities, the criticism about the model especially focused on the pretense lack of legitimacy, always persisted. This, in most cases, is done in order to improve its aim approaching the collective ideal. In this evolutionary bias is that we observe the construction of alternative models - we prefer to see as complementary to traditional representative by the parties - especially with the adoption of practices of direct democracy conducting to a system called semi- direct one. This is adopted by the current Brazilian Constitution with the prediction of the use of the figures of the plebiscite, referendum and popular initiative, does not seem to have exhausted the questioning and criticism. Rather these have been increased in recent decades flaring up in the nurture and coming to advocate the adoption of different experiences. These practices with mechanisms called participatory and deliberative, has the abili- ty to seek eventual democratic optimization.